Maternal height and prior viginal delivery as predictive factors in trail of labour after one caesarean section (1997)
A retrospective study of 304 booked parturients with one previous lower segment caesarean section for non-recurrent indications was carried out with regards to factors predicting successful trial of vaginal delivery. The height of the parturients, as well as a history of a previous vaginal delivery appeared to be predictive factors of success. Seventy per cent of the parturients succeeded in delivering vaginally. The mean fetal birthweight was 3362 g for women with vaginal delivery, while the mean maternal height was 1.58 m. Of those who needed a repeat caesarean section, surgical intervention in 46.15% of the patients was indicated by poor cervicometric progress, which might have been appropriately addressed by oxytocin augmentation and careful monitoring in labour. Regarding prior vaginal delivery, only 31.1% of parturients with a negative history, but 63.15% with a positive history, had a successful trial. Three cases of ruptured uterus were all the result of unacceptable delay in carrying out an abdominal delivery when it was clearly indicated. A large prospective study into this aspect of obstetric care will probably define additive effects of these two definite factors.